Stress-Strain Relationship for Steel-Fiber Reinforced Polymer Modified Concrete under Compression - Ismail Al- Hadithi, Dr.Abdulkader; Abdulrahman Al- Dulaimy, Ameer; .Saeed Khalaf Rejib, Dr (Iraqi Journal of Civil Engineering, 2016)
The present study, concern about an experimental work to study the stress-strain relationship of steel-fiber reinforced polymer modified concrete under compression. Four different mixes with weight proportions of (1:2:4) were used as; normal weight concrete (NC), polymer modified concrete (PMC) with (10%) of cement weight and two mixes of steel-fiber polymer modified concrete with (1%) and (2%) volume fraction of steel fiber, (SMPC). The influences of polymer and fiber addition on peak stress, strain at peak stress and the stress-strain curve were investigated for concrete mixes used. For all selected mixes, cubes (150×150×150mm) were made for compressive strength test at (28) days while stress-strain test was caried out on cylinders (150 mm  300 mm) at the same age. Results showed an improvement in compressive strength of polymer modified concrete (PMC) over reference mix, the maximum increase of it was (13.2 %) at age of (28) days. There is also an increase in compressive strength with increasing of steel fibers content with comparison to normal concrete, the maximum increases of it were (19.6% and 25.2%) of mixes with 1% and 2% fiber content by volume respectively. In terms of modulus of elasticity, the addition of polymer and the presence of fibers cause a significant increase in it. The peak of stress- strain curve for normal strength concrete (Mix No.1) was linear whereas it was more sharp for the other mixes. The behaviour of normal strength concrete (Mix No.1) was linear up to 20 % of ultimate strength, while for the mixes with the higher strength i.e. polymer modified concrete and fibers reinforced concrete (Mixes No.2, 3 and 4) the linear portion increases up to about 50 % of ultimate strength